Prevention of infective endocarditis associated with dental interventions: South African Heart Association position statement, endorsed by the South African Dental Association - Jankelow, David; Cupido, Blanche; Zuhlke, Liesl; Sliwa, Karen; Ntsekhe, Mpiko; Manga, Pravin; Doubell, Anton; Lawrenson, John; Essop, Mohammed Rafique (SA Heart Journal, 2017)
Infective endocarditis (IE) is associated with significant morbidity and mortality. Prevention is therefore an important clinical entity. The maintenance of optimal oral health is likely to play the most important role in protecting those at risk for IE. Both patients and health care practitioners must be educated in this regard. Guidelines have recommended that antibiotic prophylaxis should be limited to individuals (undergoing certain high-risk dental procedures) with underlying cardiac conditions that are associated with the greatest risk of an adverse outcome from IE. These conditions include prosthetic valves, congenital heart disease and previous IE. In South Africa, and other developing countries, IE is often a disease of young patients with rheumatic heart disease (RHD) and carries a very poor prognosis. In contrast, IE in Europe/North America, where guidelines and indications for antibiotic prophylaxis have been reduced, has a different spectrum of factors. These patients are older with degenerative valve disease. IE may also occur as a result of invasive health care associated procedures or in the setting of prosthetic valves and implantable cardiac devices. Recently published international guidelines cannot be automatically applied to countries where RHD is common and oral hygiene is poor. We therefore recommend that patients with RHD should also receive antibiotic prophylaxis prior to the listed dental procedures. Antibiotic prophylaxis should be prescribed after stressing the role of good oral health and why the approach differs in South Africa. There should be close cooperation between the dental practitioner and clinician as to who should receive prophylaxis and who should not.